Results of correction of aortic valve defects using small‑diameter «BioLAB» xenopericardial prosthesis in old patients - S. I. Babenko; R. M. Muratov; T. A. Chabaidze; N. N. Soboleva; M. N. Sorkomov (Вестник трансплантологии и искусственных органов, 2020)
A prosthesis-patient mismatch (PPM) describes a state in which the valve prosthesis implanted during surgery is too small in relation to the patient’s body size. This leads to high transvalvular pressure gradients. We investigate direct results and dependence of transvalvular pressure gradients on body mass index and surface area in patients after correction of aortic valve defects using small-diameter BioLAB prosthesis. Material and methods. From January 2011 to August 2018, 65 small-diameter (18, 20) BioLAB scaffold xenopericardial prostheses were implanted in aortic position at the Department of Emergency Surgery for Acquired Heart Defects, Bakulev National Medical Research Center of Cardiovascular Surgery. The average age of the patients was 75.4 ± 4.1 (65–86 years). The average patient body mass index was 25.74 ± 5.11 kg/m2 (19.57–39.54). The average body surface area was 1.79 ± 0.15 (1.54–2.18). Results. Isolated aortic valve replacement was performed in 38 (58%) patients, the rest of the surgeries were combined with other techniques. There were no reoperations due to early prosthetic endocarditis or prosthetic dysfunction in hospital. Hospital mortality was 6% (4 patients). Correlation dependence of peak pressure prosthesis gradient on body surface area and body mass index was 10% and 8%, respectively. Conclusions. This study confirmed the safety and effectiveness of using small-diameter BioLAB scaffold xenopericardial prostheses in aortic valve position.